Effects of Eurycoma longifolia on the reproductive cycle of female rats - Abdul Rahman, Suzanah; Ahmad, Nur Amalina; Abdul Samat, Nadia Hanis; Mohamad Zahri, Syazana; Abdullah, 'Afif Raihan (2016)
The benefits of Eurycoma longifolia for male reproductive enhancement have long been known but little can be said for its use in females and the effects of the plant on the female reproductive system and functions. This study is carried out to investigate the effects of standardized extract from the roots of Eurycoma longifolia on the oestrous cycle and hormone levels in rats. Female Sprague Dawley rats of 7-8 weeks old, weighing between 170-200g, were randomized into four groups of 6 animals each following examination of vaginal smears daily for two weeks covering 3 oestrous cycles. Rats in the treatment group received the extract orally at doses of 50, 75 and 100 mg/kg body weight for 14-days while the control group received an equal volume of distilled water in a similar manner. The oestrous cycle pattern of both control and treatment groups were observed daily and recorded for the whole of the duration including the body weights before and after the 14-days treatment. Blood samples were at the end of the study collected and the serum analysed for testosterone, oestradiol, progesterone, luteinizing hormone (LH) and follicle stimulating hormone (FSH) levels. Ovaries were removed, weighed and examined for histomorphological changes. Although some changes were observed on the analysed variables, data obtained did not indicate that the standardized extract of Eurycoma longifolia caused any detrimental effects on the female reproductive cycle and the ovary of the rats. Further investigations on effects of Eurycoma longifolia on the histopathology of the ovary may highlight the potential value of the plant in female reproductive disorders.